2020
DOI: 10.1038/s41398-020-0696-y
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness improves inflammatory biomarker levels in older adults with mild cognitive impairment: a randomized controlled trial

Abstract: Few randomized controlled trials investigated the effects of mindfulness intervention on older adults diagnosed with mild cognitive impairment (MCI). Furthermore, there have been hypotheses and theoretical mechanisms on the benefits of mindfulness intervention on biomarkers of stress, inflammation, and neuroplasticity implicated in MCI that warrant empirical evidence. We conducted a pilot randomized controlled trial to examine whether Mindful Awareness Practice (MAP) improved biomarker levels in older adults w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 80 publications
1
44
0
Order By: Relevance
“…Our network meta-analysis suggests that music therapy is the optimal intervention to treat MCI patients and improve their cognitive function, whereas acupuncture was the second best option.Further research is required to assess other interventions not included in this meta-analysis. A recent study found that mindfulness therapy improved inflammatory biomarkers in patients with MCI (Ng et al, 2020). This provides an interesting perspective on the current management paradigms for MCI.…”
Section: Discussionmentioning
confidence: 82%
“…Our network meta-analysis suggests that music therapy is the optimal intervention to treat MCI patients and improve their cognitive function, whereas acupuncture was the second best option.Further research is required to assess other interventions not included in this meta-analysis. A recent study found that mindfulness therapy improved inflammatory biomarkers in patients with MCI (Ng et al, 2020). This provides an interesting perspective on the current management paradigms for MCI.…”
Section: Discussionmentioning
confidence: 82%
“…The three following studies (Håkansson et al, 2016 ; Montero-Marin et al, 2019 ; Ng et al, 2020 ) are very dissimilar in character of intervention and control group to the first eight studies. They are included in the qualitative analysis only.…”
Section: Resultsmentioning
confidence: 99%
“…This might be driven by neuroinflammation: stress hormones (such as cortisol) affect major immune functions by increasing microglia activation, 36 although inflammation can, of course, also be triggered by other factors. Interestingly, in subjects with mild cognitive impairment, mindfulness reduced levels of inflammatory biomarker C‐reactive protein (CRP) 44 . In PD, a meta‐analysis showed increased CRP levels, but it is unclear whether this is associated with stress 45 .…”
Section: Cerebral Effects Of Chronic Stress In Pdmentioning
confidence: 99%